Parent stress and coping trajectories in Hispanic and non-Hispanic families of children at risk of autism spectrum disorder. (August 2021) - Hickey, Emily J; Stransky, Michelle; Kuhn, Jocelyn; Rosenberg, Jessica E; Cabral, Howard J; Weitzman, Carol; Broder-Fingert, Sarabeth; Feinberg, Emily
Significant disparities exist between Hispanic and non-Hispanic families in time-to-diagnosis among children identified as at risk of autism spectrum disorder; yet, little is known about parent experiences throughout the diagnostic process that may contribute to or help explain these disparities. The current study examined longitudinal trajectories of parenting stress, coping, and perceived family impact during the autism spectrum disorder diagnostic process among an ethnically and racially diverse low-income, urban sample, allowing for comparisons between Hispanic and non-Hispanic families. Hispanic families reported lower levels of parenting stress (χ 2  = 5.35(1), p  = 0.021), avoidant (χ 2  = 9.66(1), p  = 0.002) and approach (χ 2  = 8.61(1), p  = 0.003) coping, and negative family impact (χ 2  = 5.39(1), p  = 0.020) across time (main effects) compared with non-Hispanic families. Furthermore, there were differences in the change in use (Time Period × Ethnicity interaction effects) of both avoidant (χ 2  = 10.80(3), p  = 0.013) and approach (χ 2  = 11.57(3), p  = 0.009) coping, as well as negative family impact (χ 2  = 9.81(3), p  = 0.020), between Hispanic and non-Hispanic parents over time. These differences begin to shed light on the unique experiences of Hispanic parents. Because of the strengths that Hispanic families demonstrate, interventions that leverage those strengths and focus on education, empowerment, and resilience might be particularly beneficial for Hispanic families and may also better inform work to increase resilience in non-Hispanic families. Lay abstract: Little is known about parent experiences throughout the diagnostic process for autism or how these parent experiences may help explain the disparities that exist between Hispanic and non-Hispanic families in time-to-diagnosis among children identified as at risk for autism. The current study examined trajectories of parenting stress, coping, and perceived family impact over time, throughout the autism diagnostic process among Hispanic and non-Hispanic families. Hispanic families reported lower levels of parenting stress, coping, and negative family impact across time. Further, there were differences in the change in use of coping and the amount of negative family impact reported between Hispanic and non-Hispanic parents over time. These differences shed light on the unique experiences and strengths of Hispanic families demonstrate. Interventions that leverage those strengths and focus on education, empowerment, and resilience might be particularly beneficial for Hispanic families and may also better inform work to increase resilience.